Electric field-induced toughening in GaN piezoelectric semiconductor ceramics - Qin, G.; Zhang, X.; Lu, Chunsheng; Fan, C.; Zhao, M. (Elsevier Science Ltd, 2019)
In this paper, the effect of an applied electric field on fracture toughness of polarized GaN piezoelectric semiconductor ceramics was studied by using experimental and numerical methods. The results show that fracture toughness increases by 22% under a field intensity of 0.83 kV cm-1, and with further increase of the electrical filed, fracture toughness remains unchanged. This is completely different from the fracture characteristics of traditional piezoelectric ceramics that is thought to decrease with an applied electric field. The reason for such a difference is attributed to the redistribution of free electrons. It is expected that this finding will be instructive to the reliability design of piezoelectric semiconductor structures and devices.